1993
DOI: 10.1002/hed.2880150209
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin expression in normal and (pre)malignant head and neck epithelia: An overview

Abstract: Intermediate filament proteins (IFPs) are important markers of tissue differentiation and have been receiving increasing interest, in particular, through their applicability in the characterization of malignant tumors. Cytokeratins (Cks) are a family of IFPs that are typically specific for epithelial cells. They are expressed in certain combinations depending on the type of epithelium and the degree of differentiation. This review presents a critical analysis of the available data on Ck expression in normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…It has been reported that CK19 is expressed, not in normal tissue or dysplasias, but in carcinomas in situ 20) ; that is, changes in CK19 expression occur in lesions undergoing transition to cancer. In addition, one study reported that CK19 was expressed in early invasive oral cancers, but not in advanced cancers 22) . We speculate that changes in expression of CK19 in basal cells are involved in malignant transformation and cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CK19 is expressed, not in normal tissue or dysplasias, but in carcinomas in situ 20) ; that is, changes in CK19 expression occur in lesions undergoing transition to cancer. In addition, one study reported that CK19 was expressed in early invasive oral cancers, but not in advanced cancers 22) . We speculate that changes in expression of CK19 in basal cells are involved in malignant transformation and cancer proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity for CK17 was found in all layers except for the basal layer in both OOCs and DCs, whereas it was partially weak but present in all layers in KCOTs, suggesting that KCOT has a more neoplastic nature. CK19 (40 kDa) is expressed in dental lamina, the enamel organ and epithelial rests of Malassez, suggesting that it may be considered an odontogenic epithelial marker (29,(33)(34)(35). In fact, several reports have indicated that CK19 is positive in the basal layer of non-keratinized epithelium, or was negative in KCOTs (25,29).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, specific factors such as qualitative and quantitative cytokeratin expression (Van der Velden et al, 1993, Klijanienko et al, 1993 tumour vascularisation (tumour invasion of vessels and angiogenesis) (Weidner et al, 1991) and tumour DNA content have been evaluated. The value of ploidy as an independent prognostic parameter in heterogeneous solid tumours remains moot and controversial (Merkel and McGuire, 1990) and seems to be linked to treatment modalities (Ensley and Maciorowski, 1994).…”
mentioning
confidence: 99%